Vitality and teaching Indigenous literatures: A métissage - Downey, Adrian M.; Legge, Susan; Smith, Yelena (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
Methodologically framed as métissage, this work shares our experiences of teaching Indigenous literatures in K–12 and post-secondary education. Using personal narratives, we situate the research on teaching Indigenous literatures within our geographical context, Mi’kma’ki. We share how we came to this work as teachers and scholars, then discuss our journeys as readers of Indigenous literatures. We then highlight our teaching practices based on our own experiences, such as circlework and centring orality. We conclude by pointing to humour as a pathway to making the classroom a vital space.